The Analysis of Fishculture Bussiness of Sangkuriang Catfish (Clarias sp) in Bersatu Group Kelurahan Tanjung Pauh West Payakumbuh Subdistrict West Sumatera Province - Florina '; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February 21st until 25th in Bersatu Group, Kelurahan tanjung Pauh West Payakumbuh subdistrict. The purpose of this research is find out the magnitude of investment costs, income and profits and how the feasibility of developing a catfish farming business sangkuriang Bersatu Group in kelurahan Tanjung Pauh. Method used in this research is survey method.Sangkuriang catfish farming business in the Bersatu Group has 3 categories of pools are small, medium and large pool categories. Where the average income Average income derived from the small pool category is IDR 10.800.000 with an average profit of IDR.2.523.000/harvest. The category of middle pool is IDR.25.200.000 with an average profit of IDR 6.802.300/harvest. Large pool category of IDR 39.600.000 with an average profit of IDR 10.847.575/harvest. The result of feasibility analysis obtained is the RCR value of small pool category 1.28. A medium pool 1.36 and a large pond of 1,37. FRR value for small pool category is 24,82%. The middle pool is 31,93% and the large pool is 32,14%. PPC value for small pool category is 4.24 period. The medium pool is 3,13 periods and the large pool is 3,11 periods.Keywords :Bussiness Analysis, Sangkuriang Catfish, Bersatu Group